Interorganizational Communication in Implementation of The Minapolitan Program in Kalanganyar Village, Sedati District, Sidoarjo Regency - Susi Hardjati; Kalvin Edo Wahyudi; Ananta Prathama (Nusantara Science and Technology Proceedings, 2022)
Minapolitan program aims to increase the productivity and quality of fishery and marine products. Through the Minapolitan program, it is hoped that there will be centers of economic growth based on marine and fishery potential. The Minapolitan program is held in several regions in Indonesia, one of which is in Kalanganyar Village, Sedati District, Sidoarjo Regency. This study aims to describe inter-organizational communication in implementing the Minapolitan program in Kalanganyar Village. This study uses a qualitative approach. Data collection techniques are observation, interviews, document collection, and focus group discussions. The data analysis technique uses an interactive model. The results showed that inter-organizational communication that occurred in the implementation of the Minapolitan program consisted of 3 models, namely vertical upwards (implementing organizations to the upper structure), horizontal (inter-organizations implementing at the same level), and vertical downwards (implementing organizations to the lower structure). Vertical up and horizontal communication has been done well. On the other hand, vertical downward communication, especially in infrastructure development projects, has not been carried out correctly. This means that implementing organizations have not established good communication with local government organizations (villages) and community organizations related to the implementation of the Minapolitan program. As a result, the effectiveness of the Minapolitan program has the potential to be suboptimal. Suggestions, because the quality of communication is one of the keys to the success of program implementation, vertically downward communication should be considered